The 100 Per Cent Reserve Plan - Angell, James W. (Quarterly Journal of Economics, 1935)
I. The major defects of our present monetary and banking system, 1.— II. The 100 per cent reserve plan; Professor Fisher's formulation, 4.— III. Objectives of Fisher's plan over time: reflation and retail price stabilization, 16.— IV. Summary of main criticisms of the 100 per cent proposals, 26.— V. An alternative plan; methods and objectives, 29.